Effect of core strength on the measure of power in the extremities - Shinkle, J.; Nesser, T. W.; Demchak, T. J.; McMannus, D. M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to (a) develop a functional field test to assess the role of the core musculature and its impact on sport performance in an athletic population and (b) develop a functional field test to determine how well the core can transfer forces from the lower to the upper extremities. Twenty-five DI collegiate football players performed medicine ball throws (forward, reverse, right, and left) in static and dynamic positions. The results of the medicine ball throws were compared with several athletic performance measurements: 1 repetition maximum (1RM) squat, squat kg/bw, 1RM bench press, bench kg/bw, countermovement vertical jump (CMJ), 40-yd dash (40 yd), and proagility (PrA). Push press power (PWR) was used to measure the transfer of forces through the body. Several correlations were found in both the static and dynamic medicine ball throws when compared with the performance measures. Static reverse correlated with CMJ (r = 0.44), 40 yd (r = 0.5), and PrA (r = 0.46). Static left correlated with bench kg/bw (0.42), CMJ (0.44), 40 yd (0.62), and PrA (0.59). Static right also correlated with bench kg/bw (0.41), 40 yd (0.44), and PrA (0.65). Dynamic forward (DyFw) correlated with the 1RM squat (r = 0.45) and 1RM bench (0.41). Dynamic left and Dynamic right correlated with CMJ, r = 0.48 and r = 0.40, respectively. Push press power correlated with bench kg/bw (0.50), CMJ (0.48), and PrA (0.48). A stepwise regression for PWR prediction identified 1RM squat as the best predictor. The results indicate that core strength does have a significant effect on an athlete's ability to create and transfer forces to the extremities. Currently, plank exercises are considered an adequate method of training the core for athletes to improve core strength and stability. This is a problem because it puts the athletes in a nonfunctional static position that is very rarely replicated in the demands of sport-related activities. The core is the center of most kinetic chains in the body and should be trained accordingly.